Methods for high-precision subsurface imaging using spatially dense seismic data - Ziramov, Sasha (Curtin University, 2023)
Current state-of-the-art depth migration techniques are regularly applied in marine seismic exploration, where they deliver accurate and reliable pictures of Earth’s interior. The question is how these algorithms will perform in different environments, not related to oil and gas exploration. For example, how to utilise those techniques in an elusive environment of hard rocks? The main challenge there is to image highly complex, subvertical piece-wise geology, represented by often low reflectivity, in a noisy environment.